Obesity and susceptibility to severe outcomes following respiratory viral infection. Issue 7 (22nd February 2013) - Almond, Mark H; Edwards, Michael R; Barclay, Wendy S; Johnston, Sebastian L
Abstract : During the 2009 H1N1 influenza pandemic, obesity was convincingly identified as a novel, independent risk factor for multiple markers of disease severity. Associations between numerous nosocomial and community-acquired clinical infections have previously been established; yet, little is known about the mechanisms underpinning the increased susceptibility to severe outcomes following pandemic H1N1/09 infection in obesity. Here, we present a brief synthesis of the recent advances in our understanding of the immunomodulatory effects of obesity on outcomes following respiratory viral infection, with a particular focus on pandemic influenza.